Magnesium Oxide NPs Carbon Paste Ion-Selective Electrode Industrialization and Potentiostat Cyclic Voltammetry Detections for Determination of Mg+Ion in Various Solutions - Abood, Emad Salaam; Sim, Hussein Tami (Annales de chimie (Paris. 1914), 2025)
A modified ion-selective electrode with graphene powder and Magnesium Oxide Nanoparticles, a newform highly sensitive paste and selective to electron motion in redox process by cyclic voltammetry Potentiostat technical applied. A sol-gel bottom-up nanoparticle synthase method used to prepare MgO-NPs, SEM and XRD appear 18 nm average particles size, carbon powder with paraffine oil drops and MgO-NPs mixed to form homogenous black paste. Full one end glass cylinder with 0.4 r2 dimeter with copper wire to form a working electrode, plamSens 4 Potentiostat cyclic voltammetry used to motion redox processing in cell reaction by link calomel reference electrode and platinum wire axillary electrode and working electrode. 0.1 v/s, (± 2E) V parameters select, (10-100 ppm) standard and working Magnesium solutions a trace concentration used in this study. Epa/Epc > 200 V with hydrogen over potential refer to a reversable CV mechanism, kinetic and thermodynamic were study with (293-333) K the negative signal shifting in cyclic voltammograms, Randles-Sevcik equation used to found Diffusion coefficient equal 3.6 × 10-5, and rate constant, calibration curve range 1.2 × 10-3 and 10 ~ 100 ppm respectively.